Resonance Propagation and Elimination in Integrated and Islanded Microgrids - K. V. Siva Reddy; SK. Moulali; K. Harinadha Reddy; Ch. Rami Reddy; B. V. RajannaRajanna; G. Venkateswarlu; Ch. Amarendra (Institute of Advanced Engineering and Science, 2018)
In this paper, a micro grid resonance propagation model is investigated. To actively mitigate the resonance using DG units, an enhanced DG unit control scheme that uses the concept of virtual impedance is proposed. It can be seen that a conventional voltage-controlled DG unit with an LC filter has a short-circuit feature at the chosen harmonic frequencies, whereas a current-controlled DG unit presents an open-circuit characteristic. The application of underground cables and shunt capacitor banks may introduce power distribution system resonances. This paper additionally focuses on developing a voltage-controlled DG unit-based active harmonic damping technique for grid-connected and islanding micro grid systems. An improved virtual impedance control method with a virtual damping resistor and a nonlinear virtual capacitor is proposed. The nonlinear virtual capacitor is used to compensate the harmonic dip on the grid-side inductor of a DG unit LCL filter. The virtual resistance is principally answerable for micro grid resonance damping. The effectiveness of the proposed damping method is examined using each a single DG unit and multiple parallel DG units.